2004
DOI: 10.1074/jbc.m305966200
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Splice Form of Mdm2 Induces p53-independent Cell Growth and Tumorigenesis

Abstract: The Mdm2 gene is amplified in approximately onethird of human sarcomas and overexpressed in a variety of other human cancers. Mdm2 functions as an oncoprotein, in part, by acting as a negative regulator of the p53 tumor suppressor protein. Multiple spliced forms of Mdm2 transcripts have been observed in human tumors; however, the contribution of these variant transcripts to tumorigenesis is unknown. In this report, we isolate alternative splice forms of Mdm2 transcripts from sarcomas that spontaneously arise i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 46 publications
6
82
0
1
Order By: Relevance
“…Nutlin-3A and MDM2/MDMX isoforms F Bozzi et al Taken together, these findings predict that the response of WD/DD LPS to Nutlin-3A depends on the amount of the coexpressed MDM2-B isoform. The lower affinity of MDM2-B, which was further confirmed by MD simulations, is keeping with preclinical in vitro and in vivo data 37 and supports the idea that MDM2-B may contribute to the formation of cancer by means of a TP53-independent mechanism. 38 In particular, transduction of MDM2-B into a variety of cell types reveals that MDM2-B promotes TP53-independent cell growth, inhibits apoptosis, and upregulates the RelA subunit of NF k B.…”
Section: Discussionsupporting
confidence: 65%
“…Nutlin-3A and MDM2/MDMX isoforms F Bozzi et al Taken together, these findings predict that the response of WD/DD LPS to Nutlin-3A depends on the amount of the coexpressed MDM2-B isoform. The lower affinity of MDM2-B, which was further confirmed by MD simulations, is keeping with preclinical in vitro and in vivo data 37 and supports the idea that MDM2-B may contribute to the formation of cancer by means of a TP53-independent mechanism. 38 In particular, transduction of MDM2-B into a variety of cell types reveals that MDM2-B promotes TP53-independent cell growth, inhibits apoptosis, and upregulates the RelA subunit of NF k B.…”
Section: Discussionsupporting
confidence: 65%
“…All of these activities are increased by Mdm2's phosphorylation on Ser 166 and are decreased by mutation of this residue (Mayo and Donner, 2001;Ashcroft et al, 2002). Owing to its capacity to abrogate the antiproliferative effects of p53, Mdm2 overexpression is transforming (Ganguli et al, 2000;Moore et al, 2003;Steinman et al, 2004). As many as one-third of soft tissue sarcomas show amplification and/or overexpression of Mdm2, as do a substantial fraction of breast and prostate cancers (Vousden, 2000).…”
Section: Onzin Overexpression Promotes Growth Survival and Transformentioning
confidence: 99%
“…We recently showed, in a panel of pediatric rhabdomyosarcoma tumors, Ͼ90% of the metastatic tumors were positive for MDM2-ALT1 (15). Furthermore, MDM2-ALT1 and MDM2-ALT2 (another MDM2 splice variant frequently observed in tumors) have been shown to accelerate tumorigenesis in in vitro and in vivo studies (15)(16)(17)(18)(19). Indeed, a recent study showed that the expression of splice variant MDM2-ALT1 in colorectal cancer cells considerably increased the tumorigenic properties of these cells by causing the accumulation of mutant p53 (gain-of-function p53 mutants) (19).…”
mentioning
confidence: 99%